Behind an Accelerated Scientific Research Career: Dynamic Interplay of Endogenous and Exogenous Forces in Talent Development - David Yun Dai; Xian (Stella) (MDPI AG, 2020)
This study looks at the educational experiences, from the preschool years to advanced professional training in STEM fields, of a targeted sample of 10 (7 male, 3 female) early college entrants in China who later became professors at prestigious USA research universities. The purpose of the study was to find out (1) what some identifiable endogenous factors were about these individuals that facilitated the success of their accelerated learning and development; (2) what kinds of exogenous factors (e.g., environmental opportunities, resources, support) they experienced from childhood to adulthood that enhanced the successful acceleration experience; and (3) how these endogenous and exogenous factors facilitated their developmental transitions every step of the way, especially from the role of a student to that of an aspiring scientist. These questions are addressed in light of evolving complexity theory. Retrospective interviews were used for data collection. Thematic analysis of the codes from interview data yielded a conceptual map. A distinct set of endogenous and exogenous factors at different developmental junctures were identified, and their dynamic interplay was delineated to account for accelerated trajectories toward a scientific research career. The theoretical significance and practical implications of the study for talent development in science are discussed.